INFLUENCE OF THE GEOMAGNETIC FIELD ON LIVING ORGANISMS - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii)
The influence of terrestrial magnetism on biological systems is reviewed. The review is preceded by information on the physical nature of magnetism, as well as on the characteristics of the Earth’s magnetic field, the geological processes that generate it, and physical phenomena at the outer boundary of the magnetosphere. The manifestation of magnetism at the chemical level and the physical nature of dia-, para-, and ferromagnetism are considered. The corresponding classification of chemical elements is accompanied by information on their biological function. The classes of compounds that are part of living systems and are potentially capable of interacting with the magnetosphere are considered, and the special role of coordination compounds is substantiated. The features of the interaction of dia- , para-, and ferromagnets that are part of living systems with a magnetic field are considered, with special attention paid to the main facts and hypotheses concerning the mechanisms of magnetoreception. Keywords: magnetic field, magnetic-, electromagnetic-, photoreception, paramagnets, diamagnets, ferromagnets, coordination compounds, photon, biological systems.